Aceptación de forrajes tropicales por el ganado - Paladines, O.L.; Alba, Jorge de (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
An analysis was made of the consumption of tropical forages by young cattle in conditions of warm and humid climate. For green fodder the average intake was 251 kg. of dry matter per 100 kg of live weight; the consumption was 27 kg of dry matter per 100 kg. of weight increase For silage the average intake was 128 kg of dry matter per 100 kg of live weight, with a consumption of 220 per cent, the difference being mainly due to the concentrates Data indicate that forage consumption by unit of weight was less in this group than in tests made in moderate climate Three grasses were involved in this study: Pennisetum purpureum Schum, Axonopus scoparius Flugge, and Panicum maximum Jacq It is urged to make more tests on farage consumption in the course of making studies of tropical forages.